A Contrastive Study of the Address System in Indonesian and Korean: Kajian Kontrastif tentang Sistem Sapaan dalam Bahasa Indonesia dan Bahasa Korea - Putu Adi Santoso; Ni Made Sri Wulandari; Kim Min Seo (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study provides a comparative analysis of the Indonesian and Korean address systems, aiming to identify their linguistic structures, socio-pragmatic functions, and cultural foundations. The research specifically investigates how address terms encode politeness, hierarchy, and interpersonal relations in both languages. Using a qualitative-comparative method, data were collected from natural Indonesian conversations and semi‑structured interviews in Bali, while Korean data were derived from published sociolinguistic studies and interviews with Korean language instructors. The analysis reveals that Indonesian predominantly employs flexible lexical address forms-such as Pak, Bu, Mas, and Mbak-that reflect solidarity and contextual negotiation, while Korean relies on a highly structured honorific system rooted in age, hierarchy, and Confucian values. The findings contribute theoretically to contrastive pragmatics and culturally embedded politeness systems, and practically to intercultural communication and language teaching. The study recommends future quantitative research on generational shifts and register‑based address usage.